Shsh, Do Not Say Crisis! Role of Press Freedom on Bank Default Risk - Mammadova, Nargiz; Guliyev, Nijat (International Journal of Economics and Financial Issues, 2026)
This study investigates the relationship between press freedom and bank default risk across countries, with particular attention to the role of institutional quality, financial development, and information transmission mechanisms. Using an unbalanced panel of 128 countries over the period 2000–2022, the paper applies dynamic panel data techniques to examine how press freedom affects banking stability, measured by the banking Z-score. To account for cross-country heterogeneity, countries are grouped by income level, geographic region, and resource dependence. In addition, a panel Blinder–Oaxaca decomposition is employed to identify the factors driving differences in average bank default risk across country groups, while a Threshold ARCH (TARCH) model is used to assess asymmetric responses of bank risk to positive and negative news. The results show that press freedom alone is not a consistent predictor of bank default risk across countries. Instead, its impact depends on the broader informational and institutional environment. In countries with higher education levels and greater internet penetration, increased press freedom is associated with higher bank default risk, indicating that more informed and digitally connected populations may react more strongly to financial news, amplifying herding behavior and bank fragility. Evidence from the TARCH model further suggests that bank default risk responds asymmetrically to news shocks, with negative news exerting a stronger effect than positive news. Overall, the findings underscore the importance of institutional context when evaluating the role of press freedom in financial stability.